Relations of Gender and Socioeconomic Status to Physics Through Metacognition and Self-Efficacy - Yerdelen-Damar, Sevda; Pesman, Haki (Routledge Journals, Taylor & Francis Ltd, 2013)
The authors explored how gender and socioeconomic status (SES) predicted physics achievement as mediated by metacognition and physics self-efficacy. Data were collected from 338 high school students. The model designed for exploring how gender and SES-related differences in physics achievement were explained through metacognition and physics self-efficacy was tested. The result showed that metacognition and physics self-efficacy could explain gender- and SES-related differences in physics achievement. In addition, it was observed that physics self-efficacy mediated the relation of metacognition to physics achievement whereas metacognition did not. This finding means that metacognition contributed to physics achievement through physics self-efficacy.
Keywords: gender; metacognition; physics self-efficacy; socioeconomic status; structural equation modeling